Teachers’ Perspectives on the Efficacy of Oral Presentation Tasks toward Promoted Linguistic Acquisition - Makena, Bulelwa; Feni, Viwe Lungisani (Research in Social Sciences and Technology, 2023)
To unlock language proficiency among learners, speaking is regarded to be an essential and crucial aspect to master, not only for learning purposes but for recognized communication dynamics. Language learning has numerous critical aspects. To be lacking in speaking proficiencies has been noted to impart negatively toward language learning. This paper explores whether oral presentations can be regarded as a vital tool to unlock learner language development. To collect data, qualitative research approaches embedded in a case study design were used. These are methods well known to assist in attaining better understanding in real-life situations. Three English language teachers were perceived relevant since they teach English to first-year university students. Although studies have been conducted on advantages of using oral tasks in a schooling environment, little to nothing is mentioned in the literature about how such tasks can be viable instruments to augment critical thinking and problem-solving skills. Findings suggest that motivated learning and enhanced communication skills were major factors that could lead to enhanced language aptitudes. This paper concludes that for teaching and learning to incorporate oral tasks brings numerous benefits for language learning as well as other subjects underpinning the prescribed curriculum. It is proposed that it is necessary to consider diverse perspectives in discussions related to teaching methods as oral activities are prominent tools for language expansion.